2019
DOI: 10.1039/c9sc03760h
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced coupling through π-stacking in imidazole-based molecular junctions

Abstract: We demonstrate that imidazole based π–π stacked dimers form strong and efficient conductance pathways in single-molecule junctions using the scanning-tunneling microscope-break junction (STM-BJ) technique and density functional theory-based calculations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 30 publications
(30 reference statements)
4
42
4
Order By: Relevance
“…Evidence of 1-methylimidazole adsorption on the metallic electrode is further provided by the increased G 0 signal, as adsorbates are known to stabilise point contacts. 32 We found no evidence of formation of π-stacked junctions as previously described in the literature, 24 and we ascribe this phenomenon to the different environment used in our study, where tetrahydrofuran can form a solvation shell around the imidazole and prevent the formation of π-stacked supramolecular structures.…”
Section: Scanning Tunnelling Microscopy Break Junction Measurementssupporting
confidence: 66%
See 1 more Smart Citation
“…Evidence of 1-methylimidazole adsorption on the metallic electrode is further provided by the increased G 0 signal, as adsorbates are known to stabilise point contacts. 32 We found no evidence of formation of π-stacked junctions as previously described in the literature, 24 and we ascribe this phenomenon to the different environment used in our study, where tetrahydrofuran can form a solvation shell around the imidazole and prevent the formation of π-stacked supramolecular structures.…”
Section: Scanning Tunnelling Microscopy Break Junction Measurementssupporting
confidence: 66%
“…23 Recently, it has also been successfully used as a molecular contact in scanning tunnelling microscopy break junction (STM-BJ) studies, as an aurophilic terminus. 24 We came across an anomalous behaviour of imidazolic compounds during our single-molecule conductance studies. In its protonated form, we would not expect junctions to form since the pair of electrons on the pyrrolic nitrogen are part of the aromatic sextet and thus not obviously available for bonding to a metal contact.…”
Section: Introductionmentioning
confidence: 99%
“…Using a scanning tunneling microscopebased break-junction (STM-BJ) technique, Fu et al have confirmed the ability of imidazole to function as an aurophilic linker for single-molecule junctions. [14] According to their study, imidazole-terminated alkanes are attached to gold electrodes via the pyridine-like nitrogen at each side, exhibiting distinct conductance features derived from different binding configurations. Furthermore, the elimination of the hydrogen atom bonded to the pyrrole-like nitrogen in imidazole under certain conditions opens the possibility to directly form bridging junctions across metallic nanogaps, which has not been demonstrated until very recently.…”
Section: Introductionmentioning
confidence: 99%
“…PSD has been used in the literature to characterize through-space coupling in molecular junctions where charge transport does not follow the chemical bond organization, but travels through eigenchannels opened by non-bonding interactions. [13,14,34,35] When charge transport is purely through-bond, the (the integral of the power spectral density) scales approximately with , while the scaling increases when charge transport has a through-space character, to approach the value found for pure through-space tunnelling of . When is normalized by the average conductance ( / ) it is therefore generally found to be insensitive to the junction conductance for through-bond coupling.…”
Section: Main Textmentioning
confidence: 94%
“…Stacks of phenyl rings and other simple heteroaromatics are able to act as efficient conductors in molecular junctions, [10,11] with charge transported through ππ interactions. [12][13][14][15][16][17] As the stacking configuration is unfolded, conductance is predicted to drop by orders of magnitude, as tunnelling through a saturated propyl chain is very inefficient. Such a device would represent a new class of molecular electronic devices responsive to mechanical stimuli, complementing the existing range that exploits changes in the electrodemolecule interface, [18][19][20][21][22][23][24] stereoelectronic configuration switching, [25] and stretching-dependent quantum interference effects [12,26] as the molecular junction is compressed and relaxed.…”
Section: Main Textmentioning
confidence: 99%